Being and becoming a student: an investigation into how a pedagogic approach built on collaborative participation in academic literacy practices supports students' academic practice, knowlege and identity - Tapp, Jane (2013)
Set in the context of a Post-92 university college Education Studies department, this thesis investigates how new undergraduates might be supported in the transition to Higher Education. It describes an intervention informed by research into Academic Literacies that was undertaken in a first year, first semester module. The intervention aimed to scaffold participation in academic practice, and in particular academic literacy practice, in collaborative workshops within the context of the module content. The methodological approach combines action research with aspects of ethnography to produce ‘ethnographic action research’. Drawing on the work of Lave & Wenger, students working in groups are conceptualised as academic student communities of practice, and audio recordings of students engaged in collaborative activities provide evidence of their lived experience of the module in three domains: what they do; what they know; and how they position themselves in relation to academic practice.